2011
DOI: 10.1111/j.1600-0463.2011.02816.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of c‐Jun N‐terminal kinase and p38/activation protein‐1 in interleukin‐1β‐mediated type I collagen synthesis in rat hepatic stellate cells

Abstract: Interleukin-1 (IL-1) may play a role in maintaining hepatic stellate cell (HSC) in activated state that is responsible for hepatic fibrogenesis. However, the signal transduction pathway that is stimulated by IL-1 in HSC remains to be fully elucidated. The aims of this study were to investigate the role of c-Jun N-terminal kinase (JNK) and p38/activation protein (AP-1) in IL-1β-mediated type I collagen synthesis in rat HSCs. Here, we show that IL-1β could activate JNK and p38 in a time-dependent manner, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Previous studies have demonstrated that baicalin may decrease levels of interleukin (IL)-1β (19) and depress the expression of collagen type I (20). As IL-1β is a pro-inflammatory agent and collagen type I expression is an indicator of dedifferentiation (21), baicalin may have a positive effect on inflammation and the dedifferentiation of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that baicalin may decrease levels of interleukin (IL)-1β (19) and depress the expression of collagen type I (20). As IL-1β is a pro-inflammatory agent and collagen type I expression is an indicator of dedifferentiation (21), baicalin may have a positive effect on inflammation and the dedifferentiation of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our data and reports of others demonstrate that the mechanisms by which IL-1β exerts its pathogenic effects involve sensitization of hepatocytes to cytotoxicity induced by TNF-α (14,29), upregulation of lipid synthesis in hepatocytes (12), activation of hepatic stellate cells (30), maintenance of macrophages in inflammatory state (31), and feed-forward induction of LPS-inducible inflammatory cytokines (17), such as TNF-α or MCP-1, that are crucial in ALD (24,32). Our results also demonstrated that even very low concentrations of IL-1β exerted significant biological effects on hepatocytes and macrophages, thus giving additional support to the crucial role of IL-1β in ALD, even at the relatively low absolute serum levels of IL-1β in vivo.…”
Section: Figurementioning
confidence: 89%
“…27 It is involved in the perpetuation of HSC activation resulting in hepatic fibrogenesis as a functional change. 28 It also promotes the deposition of ECM. 29 In the present study, levels of both IL-1 subtypes (a and b) were lowered by nilotinib and imatinib at the doses tested.…”
Section: Discussionmentioning
confidence: 99%